Zigzag shaped fin effectiveness on the melting process in PCM integrated mixing channels and ANFIS based performance estimation - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier, 2026)
Background: In many energy systems, performance enhancement of PCM-mounted systems with various fin designs and channel arrangements becomes crucial. In this study, effects of using zigzag shaped fins on melting of encapsulated PCM installed in a mixing chamber under forced convection for different inlet-outlet port cases and in various flow configurations are analyzed. Methods: Using the finite element method, the effects of the following on the flow field, temperature field, and melt fraction are examined: The mixing streams' flow rate ratio, fin size, fin number, wavy fin non-dimensional amplitude, and wavy fin wave number. The estimation of melt fraction dynamics is done using a modeling approach based on ANFIS. Significant Findings: In comparison to the lowest FRR configuration, melting time decreases by 38.8% and 43.4% in the flat and zigzag fin scenarios with the highest FRR. When comparing the maximum and lowest fin lengths with Nf = 4, the melting time for the flat and zigzag fins drops by 19.6% and 14.6%, respectively. The amount of melt fraction is increased by aligning the intake ports orthogonally. Considering the opposing inlets and outputs of the mixing chamber, the worst configuration for melt dynamics is achieved. Using a modeling approach based on ANFIS, melt fraction dynamics is successfully estimated.
Keywords: Zigzag fin; Encapsulated PCM; Mixing chamber; Finite element method; ANFIS